Peningkatan Kemampuan Guru dalam Proses Pembelajaran melalui Supervisi Kelas di Sekolah Binaan SMP Negeri 53 Batam - Supratiyo, Heri (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The national goal of education is contained in the 4th paragraph of the 45th Constitution of the Republic of Indonesia, which is to educate the nation's life. Even a generation that is intelligent and has noble character is one of the critical roles of educators in this country. But those who always want to learn to improve their abilities and those who are challenged with various problems related to education, including class supervision, are expected to be able to support the teacher's ability to maximize their role. This School Action Research was conducted at the SMP Negeri 53 Batam Foster School, Riau. This School Action Research aims to determine whether teachers' abilities can be improved through Class Supervision. It is hoped that the preparation of School Action Research at SMP Negeri 53 Batam Assisted Schools can provide additional insight into the importance of classroom supervision to be carried out. The method of data collection is done through document studies and observation. The method of data analysis is descriptive and quantitative data using supervision instruments (attached). The results obtained from this study show that class supervision can improve the ability or professional competence of teachers in learning for teachers in Batam City Junior High Schools. The evidence from the process and results obtained in cycle I increased on average to be better, namely 80%. Likewise, in cycle II, the average rose even higher, namely 80%. The conclusions obtained from this study are that a combination of classroom supervision and the preparation of school action research can improve teachers' ability or professional competence in learning